Use of corticosteroids and the outcome of infants with bronchopulmonary dysplasia - Mataloun, Marta M. G. B.; Gibelli, Maria Augusta C.; Kato, Ana V.; Vaz, Flávio Adolfo Costa; Leone, Cléa Rodrigues (Revista do Hospital das Clínicas, 1999)
Ventilator-dependent premature infants are often treated with dexamethasone. Several trials showed that steroids while improve pulmonary compliance and facilitate extubation, some treated infants may have adverse effects, such as alterations of growth curves. We conducted this retrospective study to evaluate the effects of steroids on mechanical ventilation, oxygen therapy, hospital length stay and mortality, in ventilator-dependent infants with bronchopulmonary dysplasia (BPD) (defined as the need of oxygen supplementation at 28 days of life). Twenty-six newborns with BPD were evaluated during 9 -- 42 days postpartum (mean = 31 days) and were divided into two groups: Group I - 14 newborns that did not receive dexamethasone, and Group II - 12 newborns that received dexamethasone at 14 --21 days of life. Dexamethasone was given at a dose of 0.25 mg per kilogram of body weight twice daily intravenously for 3 days, after which the dose was tapered. RESULTS: There were no statistically significant differences in the mean length of mechanical ventilation (Group I - 37 days, Group II - 35 days); oxygen supplementation (Group I - 16 days, Group II - 29 days); hospital stay (Group I - 72 days, Group II - 113 days); mortality (Group I - 35.7%, Group II - 41.6%). At birth, Group II was lighter (BW: Group I - 1154 grams ± 302, Group II - 791 grams ± 165; p < 0.05) and smaller (height: Group I - 37.22 cm ± 3.3, Group II - 33.5 ± 2.4; p< 0.05) than Group I. At 40 weeks, there were no statistically significant differences between groups in relation to anthropometric measurements. CONCLUSIONS: The use of corticosteroids in bronchopulmonary dysplasic infants may influence the somatic growth during its use. However, after its suspension, a recovery seems to occur, suggesting that its influence could be transitory.